1507. Evaluating the Effects of a "Urinalysis to Reflex Culture" Process Change in the Emergency Department (ED) at a Veterans Affairs (VA) Hospital. (26th November 2018) - Ismail, Georgiana; Patel, Ursula C; Suda, Katie J
Abstract: Background: The ED environment makes proactive collection of urine cultures (UCs) favorable. However, unnecessary UCs can result in over-detection and over-treatment of asymptomatic bacteriuria (ASB). A previous analysis at the study facility found that UCs were collected frequently despite negative urinalyses (UA), which commonly resulted in unnecessary antibiotics. Our objective was to compare the frequency of inappropriate UC utilization and inappropriate antibiotic prescribing post implementation of a "Urinalysis to Reflex Culture" process change intervention. A secondary objective was to assess the frequency of health encounters for UTIs post implementation. Methods: After education, an ED process change was implemented in October 2017. This included automatic UC cancellation if UAs had < 5 WBC/HPF. An option for "do not cancel (DNC)" UC was available for specific conditions (eg. pregnancy) per guidelines. Data were prospectively collected for 3 months post-implementation and included UA/UC results, presence of UTI symptoms, antibiotics prescribed and healthcare utilization. Inappropriate UC was defined as a UC ordered despite negative UA in asymptomatic patients. Inappropriate antibiotic prescribing was defined as treatment in patients with ASB. A Student's t -test and contingency tables were applied in SAS; significance was set at P ≤ 0.05. Results: There were 684 UAs (37.2% post-intervention) evaluated from ED visits. Post-intervention ( n = 255 UAs), 37.3% of UAs were negative with UCs cancelled. Of the remaining UAs, 37.3% were positive with a processed UC, 16.9% were ordered as DNC and 8.6% were ordered without a UC. UC processing despite a negative UA significantly decreased from 100% pre-intervention to 38.6% post-intervention ( P < 0.001). Inappropriate antibiotics for ASB also decreased from 10.2% pre-intervention to 1.9% post-intervention (OR = 0.17; P < 0.0110). In patients with negative UAs, antibiotic prescribing decreased by 25.3% post-intervention ( P = NS). No reports of outpatient, ED, or hospital visits for UTI symptoms were found within 7 days of initial UA post-intervention. Conclusion: A "UA to Reflex Culture" process change demonstrated a significant decrease in processing of inappropriate UCs and unnecessary antibiotics for ASB. There were no missed UTIs or other adverse patient outcomes. Disclosures: All authors: No reported disclosures.